Analytic Affordance: Transcripts as Conventionalised Systems in Discourse Studies. (August 2014) - Gibson, Will; Webb, Helena; vom Lehn, Dirk
This article explores the role of transcripts in the analysis of social action. Drawing on a study of the interactional processes in optometry consultations, we show how our interest in the rhythm of reading letters from a chart arose serendipitously from our orientation to transcription conventions. We discuss our development of alternative transcription systems, and the affordances of each. We relate this example to constructivist debates in the area of transcription and argue that the issues have been largely characterised in political terms at the expense of a focus on the actual processes of transcription. We show here that analytic affordances emerge through an orientation to professional conventions. The article ends by suggesting that a close reflection on the design of transcripts and on transcription innovation can lead to more nuanced analysis as it puts the researcher in dialogue with the taken for granted ideas embedded in a system.